Shakespeare, madness, and music scoring insanity in cinematic adaptations - Leonard, Kendra Preston. (Scarecrow Press, 2009)
Shakespeare's three political tragedies--Hamlet, Macbeth, and King Lear--have numerously been presented or adapted on film. These three plays all involve the recurring trope of madness, which, as constructed by Shakespeare, provided a wider canvas on which to detail those materials that could not be otherwise expressed: sexual desire and expectation, political unrest, and, ultimately, truth, as excavated by characters so afflicted. Music has long been associated with madness, and was oftenused as an audible symptom of a victim's disassociation from their surroundings and societal rules, as well.